A newly-developed model for predicting cutting power during wood sawing with circular saw blades - Orlowski, Kazimierz; Ochrymiuk, Tomasz (Maderas. Ciencia y Tecnología, 2017)
In the classical approach, cutting forces and cutting power in sawing processes of orthotropic materials such as wood are generally calculated on the basis of the specific cutting resistance kc (cutting force per unit area of cut). For every type of sawing kinematics (frame saws, band saws and circular sawing machines) different empirical values of specific cutting resistance kc have to be applied. It should be emphasised that sources in the scientific literature and handbooks do not provide any information about wood provenance, nor about cutting conditions in which cutting resistance had been determined. In analyses of sawing processes in which the offcut is formed by shear, Atkins’s ideas that all cutting forms a branch of elastoplastic fracture mechanics can be applied. Thanks to this modern approach it was possible to reveal, using experimental results data of fracture toughness and shear yield stresses of Polish pine (Pinus sylvestris), the significant effect of the raw material provenance (source of wood) on cutting power. In the common model for circular sawing machine kinematics, which is similar to metal milling, the sum of all uncut chip thicknesses of the all the teeth simultaneously engaged represented the mean uncut chip thickness. In this work predictions of the newly-developed model for the circular sawing machine are presented. In the model, beside uncut chip thicknesses changes, appropriate changes in shear yield stress and toughness with tooth/grain orientation have been taken into account. The conducted analyses have demonstrated that values of RMS of cutting power obtained with the new developed model are slightly larger than experimental values. On the other hand computed values of cutting power with the use of the mean uncut chip thicknesses in the model are a bit lower from the empirical one.